Non-Maxwellian ion distribution in the equatorial and auroral electrojets - Koontaweepunya, Rattanakorn; Dimant, Yakov S.; Oppenheim, Meers M. (Frontiers in Astronomy and Space Sciences, 2024)
Strong electric fields in the auroral and equatorial electrojets can distort the background ion distribution function away from the Maxwellian. We developed a collisional plasma kinetic model using the Boltzmann equation and a simple BGK collision operator to predict a relatively simple relationship between the intensity of the background electric field and the resulting ion distribution function. To test the model, we perform 3-D plasma particle-in-cell simulations and compared the results to the model. Both the simulation and the analytical model assume a constant ion-neutral collision rate. The simulations show less ion heating in the Pedersen direction than in the analytical model but nearly identical overall heating. The model overestimates heating in the Pedersen direction because the simple BGK operator models collisions as a kinetic friction only in the Pedersen direction. On the other hand, the fully kinetic particle-in-cell code captures the physics of ion scattering in 3-D and therefore heats ions more isotropically. Although the simple BGK analytical theory does not precisely model the non-Maxwellian ion distribution function, it does capture the overall momentum and energy flows and therefore can provide the basis of further kinetic analysis of E-region wave evolution during strongly driven conditions.